Developing mobile game application for introduction to financial accounting - Mohamed Imran Mohamed Ariff; Fuad Mohd Khalil; Rahayu Abdul Rahman; Suraya Masrom; Noreen Izza Arshad (Institute of Advanced Engineering and Science, 2022)
The financial accounting subject is one of the core subjects that is essential for any accounting student. However, this subject is perceived as boring and difficult to comprehend particularly for students who lack in the accounting knowledge. The aim of this research paper is to present the adoption of the gamification learning concept in designing and developing a mobile game application to cultivate better understanding in the financial accounting subject. This mobile application was developed for Android operating system and was designed using the modified game methodology. Further, this mobile application was subjected to several testing phases using numerous participants. The results indicate the adoption of gamification has aided the students in understanding the financial accounting subject. Furthermore, the participants also indicated that learning using gamification has encouraged them to think critically which then allowed them to better comprehend the financial accounting subject. The development of this mobile game application also contributes to the gamification literature which is vastly used in learning, and it advantages in improving the understanding of how games can be adopted to foster better understanding in the financial accounting subject.